Integrity and Safety Factors of Asymmetric Mooring Line Arrangement on Ocean Farm ITS - Mulyadi, Yeyes; Purnawanti, Yani Nurita; Armono, Haryo Dwito; Mahdyansyah, Mohammad Hilmy; Syarifudin, Muhammad Rizky (Institut Teknologi Sepuluh Nopember, 2024)
An offshore aquaculture model called OFITS has been designed to be installed in the Indonesia Ocean. The OFITS structure consists of an underwater fish cage and living quarters at the superstructure. An asymmetric mooring line arrangement is proposed to be applied at OFITS. This paper aims to analyze the integrity and safety factor of the asymmetric mooring line arrangement used on OFITS in the presence of environmental load. The proposed asymmetric mooring line arrangement has 14 lines with a specified configuration. There are 10 mooring lines installed on the front side in line with the incoming waves and 4 others installed behind the cage. A nylon line with a diameter of 42 mm and a length of 70 m is used as the mooring line attached to a steel anchor weighing 0.25 tons. The analysis method for the moored cage motion uses the time domain analysis. The mooring line's integrity analysis results show that the maximum tension result is 18.55 tons, with a safety factor of 2.07. It can be concluded that the proposed asymmetric arrangement mooring has good integrity and meets the safety factor requirements of the DNVGL standard, with a minimum safety factor of 1.45.